Alfalfa Cost-Return Budget in South Central and Southeast Kansas - Fogleman, Sarah L.; Kilgore, Gary L. (My University, 2004)
This publication contains information for a projected budget reflecting expected income and cost based on alfalfa production in south central and southeast Kansas.
MF363_2004_10
Keywords: MF363; Economics; Crops; MF